1998
DOI: 10.1210/jcem.83.9.5122
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cardiovascular Effects of Insulin-Like Growth Factor I in Patients with Chronic Heart Failure1

Abstract: Insulin-like growth factor I (IGF-I) enhances myofibrillar development in cardiomyocytes of rats in culture and in vivo. In addition, IGF-I has vasodilatory effects and improves cardiac function in healthy volunteers. This study was conducted to evaluate the acute hemodynamic effects of IGF-I in patients with chronic heart failure Eight patients with chronic heart failure were randomized to receive recombinant human IGF-I (60 micrograms/kg) or placebo, i.v., over 4 h in a cross-over, double blind study on 2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It stimulates bone growth, cell differentiation, and metabolism (Froesch, Zenobi, & Hussain, 1994). Diabetes is usually associated with low serum levels of IGF-1, and several reports have outlined the function associated with IGF-1 changes during the progress of MI and cardiovascular diseases (Donath et al, 1998;Vaessen et al, 2001). Moreover, in an ISOinduced MI in rats, treatment with IGF-1 reduced myocytes necrosis and increased capillary sprouting in the myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…It stimulates bone growth, cell differentiation, and metabolism (Froesch, Zenobi, & Hussain, 1994). Diabetes is usually associated with low serum levels of IGF-1, and several reports have outlined the function associated with IGF-1 changes during the progress of MI and cardiovascular diseases (Donath et al, 1998;Vaessen et al, 2001). Moreover, in an ISOinduced MI in rats, treatment with IGF-1 reduced myocytes necrosis and increased capillary sprouting in the myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 is also vital in myocardial function regulation and has been demonstrated to not only promote cardiomyocyte growth but also ensure cardiomyocyte survival. Clinical studies using IGF-1 treatment, have shown that it improves myocardial function post-MI (Duerr et al, 1995;Donath et al, 1998). Unfortunately, extended IGF-1 overexpression has been shown to reduce cardiac functional recovery post-MI, making controlled delivery vital for its future use as a cardiac medicine (Prêle et al, 2012).…”
Section: Growth Factor Deliverymentioning
confidence: 99%